Relationship between increase in flexibility and improvement in the execution of daily actions by adults participating in supervised exercise program - Claudio Gil Soares de Araújo; Carla Werlang Coelho (Universidade Federal de Santa Catarina, 2000)
The aim of this study was to relate flexibility improvements from a supervised exercise program (SEP) attendance, to possible improvements in the execution of daily actions by adults. The sample consisted of 20 subjects, the majority of them cardiac patients, with an average age of 58 ± 9 years, actively participating in an SEP, selected intentionally. The Flexitest, was used to determine flexibility. In addition, the subjects answered an 11-question questionnaire, aiming to assess relative difficulty in daily actions. The questionnaire was completed between three and 18 months after beginning the program and assessed the subjects' opinion on their improvements in daily actions since starting on the SEP. After the SEP, improvements were observed in the execution of 11 daily actions, global flexibility, and six individual movements on the Flexitest (p<.05). There was a correlation between differences in answers given to the questionnaire and changes in global fl exibility (r=.45; p<.04). There was an inverse relationship between body weight and flexibility changes for the group as a whole (r=-.66; p<.05). It was concluded that ease of execution of daily actions after a period of SEP is related to improvements in global flexibility. Improvements in global flexibility are also related to reductions in body weight. These results may have implications for the personalization of flexibility training, in the context of a health-oriented exercise program. RESUMO Este estudo objetivou relacionar ganhos de flexibilidade decorrentes da participaão em programa de exercício supervisionado (PES) com eventuais facilitações na execução de ações cotidianas em adultos. Vinte indivíduos, a maioria coronariopatas, com idade de 58 ± 9 anos, que estavam freqüentando um PES, foram selecionados intencionalmente. Para a avaliação da flexibilidade utilizou-se o Flexiteste. Em adendo, os indivíduos responderam um questionário com 11 perguntas para avaliar subjetivamente, a facilidade e/ou dificuldade de realizar ações cotidianas, no início do PES e no momento em que estavam respondendo o questionário. Após o PES, houve ganhos na facilidade de execução das 11 ações, na flexibilidade global passiva e em seis movimentos individuais do Flexiteste (p<0,05). Há correlação significativa entre as diferenças das respostas ao questionário e as variações na flexibilidade global (r=0,45; p<0,04). Existe relação inversa entre as variações de peso e de flexibilidade (r=-0,66; p<0,05). Concluiu-se que a facilitação na realização de ações cotidianas, após um período de PES, está associada a uma melhoria da flexibilidade global. Aumentos na flexibilidade global estão associados com uma redução de peso corporal. Estes resultados podem possuir implicações para a individualização do treinamento da flexibilidade, em um programa de exercício voltado à promoção da saúde.